When the scientific secrets of perfect timing - Daniel H. Pink (Edinburgh Canongate Books Ltd, 2018)
Timing is everything. But we don't know much about timing itself. Timing, it's often assumed, is an art; in 'When', Pink shows that timing is in fact a science. Drawing on a rich trove of research from psychology, biology and economics, Pink reveals how best to live, work and succeed.
Includes bibliographical references and index.
Keywords: Time management